If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-4)=6(x+6)
We move all terms to the left:
3(2x-4)-(6(x+6))=0
We multiply parentheses
6x-(6(x+6))-12=0
We calculate terms in parentheses: -(6(x+6)), so:We get rid of parentheses
6(x+6)
We multiply parentheses
6x+36
Back to the equation:
-(6x+36)
6x-6x-36-12=0
We add all the numbers together, and all the variables
-48!=0
There is no solution for this equation
| -5u-(-7u)=-12 | | -5(x+7=-4-7x | | 4x30=2 | | 376=3x+40 | | 128-x=202 | | 9+16j=15j | | -4=7n | | -3x+367=40 | | 4(2x-4)-5x+4=-30 | | 6+x+5x=4x | | -12-6n=84 | | 2x+1=13-9 | | 3(7–2x)=–1–4x | | 5(x−2)+6=2x−4+3x | | 21=9–3y | | (4x+10)-(3x+-5=) | | 5c−3=5c | | (4x-2)(x-3)=14 | | -c4=2 | | 9x-12=3(x-8) | | -2=3+s | | 5x-10=5x+22=180 | | 5x-10=5x+22=10 | | 12+p=13 | | 5x-10=5x+22 | | 3-7b=-25 | | 29(x+1)=200 | | (7x/10)-(x/2)=1 | | 20x+7=4x=6 | | 9u+27=-3(u-1) | | n/10+-2=-3 | | (5(y-4))/3=2y-5 |